2016
DOI: 10.3389/fevo.2016.00009
|View full text |Cite
|
Sign up to set email alerts
|

Superb Fairy-Wren (Malurus cyaneus) Sons and Daughters Acquire Song Elements of Mothers and Social Fathers

Abstract: Birdsong is regarded as a classic example of a sexually-selected trait and has been primarily studied in systems with male song. Complex solo female song is emerging from the shadows of overlooked phenomena. In males, rearing conditions affect male song complexity, and males with complex songs are often more successful at mate attraction and territorial defense. Little is known about the ontogeny or function of complex female song. Here we examine song elements in fledgling superb fairy-wrens (Malurus cyaneus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…Between‐sex differences in song sharing may also reflect sex‐specific tutor differences. Based on acoustic similarities, Evans and Kleindorfer () found that male and female Superb Fairy‐wrens ( Malarus cyaneus ) learn song elements from both their social fathers and mothers. Studies of two temperate songbirds, in contrast, suggest that young males learn songs from natal neighbors and breeding territory neighbors (Nelson & Poesel, ; Wheelwright et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between‐sex differences in song sharing may also reflect sex‐specific tutor differences. Based on acoustic similarities, Evans and Kleindorfer () found that male and female Superb Fairy‐wrens ( Malarus cyaneus ) learn song elements from both their social fathers and mothers. Studies of two temperate songbirds, in contrast, suggest that young males learn songs from natal neighbors and breeding territory neighbors (Nelson & Poesel, ; Wheelwright et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Between-sex differences in song sharing may also reflect sex-specific tutor differences. Based on acoustic similarities, Evans and Kleindorfer (2016) found that male and female Superb Fairy-wrens (Malarus cyaneus) learn song elements from both their social fathers and mothers.…”
Section: Spatial Structure Of Songsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential explanation could be that young bird's songs differ from their mothers' because they learn vocal elements from multiple tutors. They may learn from their social father, which has been shown in several closely related species (Greig et al, 2012;Evans and Kleindorfer, 2016), but also possibly from auxiliary helpers and other nearby adults.…”
Section: Discussionmentioning
confidence: 92%
“…Australian fairy-wrens (genus Malurus, Maluridae) offer an opportunity to study patterns of intraspecific variation in songs in situations with varying levels of geographic continuity between populations. In fairy-wrens both sexes sing (Payne et al 1988, Rowley and Russell 1997, Greig and Pruett-Jones 2008, Evans and Kleindorfer 2016, particularly during territorial disputes (Hall and Peters 2008, Dowling and Webster 2013, Kleindorfer et al 2013 and (for males) during dawn chorus and conspecific signaling displays Cockburn 2008, Greig andPruett-Jones 2010). All fairy-wrens are cooperatively breeding and socially monogamous, but most are reproductively promiscuous, leading to complex genetic relationships within social family groups (Rowley and Russell 1990, Dunn et al 1995, Tarvin et al 2005, Webster et al 2007, 2008, Cockburn et al 2009, Colombelli-Négrel et al 2010, Rowe and Pruett-Jones 2013.…”
Section: Introductionmentioning
confidence: 99%